(untitled) (Research, Society and Development, 2021)
The deaf and the acquisition of the Portuguese language lead us to issues of inclusive origin that for some time have been seeking a standardization of social relations, as their goals are based on public policies. In order to understand how this process was and is being inserted, it was sought, through a bibliographical research, to make this comparative and evolutionary analysis, sharpening a discussion about this subject. Some authors such as Sacks, Kleiman, Kojima, Segala among others, helped us to clarify some themes. This analysis is based on praxis, that is, theory and practice, leading to a reassessment of how we, future teachers, can contribute to the inclusion of deaf people in schools and also in the social environment, as they can still collaborate more, exercising its role as a citizen.